2008
DOI: 10.1002/ijc.23439
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐D promotes tumor growth and lymphatic spread in a mouse model of hepatocellular carcinoma

Abstract: Lymphatic spread is an important clinical determinant for the prognosis of hepatocellular carcinoma (HCC), but little is known about the control of lymphangiogenesis in HCC. We addressed expression and biological role of the pro‐(lymph), angiogenic protein VEGF‐D in this tumor entity. Using immunohistochemistry and in situ hybridization on specimens of HCC, cirrhotic and normal liver we found abundant expression of VEGF‐D exclusively in the tumor cells. The cognate receptor VEGFR‐3 was detected on blood and ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 40 publications
(56 reference statements)
1
51
0
Order By: Relevance
“…However, we unexpectedly found that cases with lymph node metastasis had a lower mean value of CET1-w_5_fos_median than did cases without lymph node metastasis. Almost all previous studies have reported the contrary result that angiogenesis is positively correlated with lymph node metastasis (48)(49)(50). The reason for this discrepancy may be NPC patients often experienced lymph node metastasis even in the low-stage (stage I-II).…”
Section: Discussionmentioning
confidence: 90%
“…However, we unexpectedly found that cases with lymph node metastasis had a lower mean value of CET1-w_5_fos_median than did cases without lymph node metastasis. Almost all previous studies have reported the contrary result that angiogenesis is positively correlated with lymph node metastasis (48)(49)(50). The reason for this discrepancy may be NPC patients often experienced lymph node metastasis even in the low-stage (stage I-II).…”
Section: Discussionmentioning
confidence: 90%
“…12 Metastatic liver cancer also expresses angiogenic factors such as vascular endothelial growth factor (VEGF) and microvessel counts. 9,13 Levels of these angiogenic factors may affect patient survival.…”
Section: Synopsismentioning
confidence: 99%
“…Expression levels of VEGF-D and VEGF-C correlate with lymph node metastasis in several human cancers [15,16], and addition or overexpression of exogenous VEGF-C or VEGF-D induces lymphatic growth and tumor metastasis in preclinical cancer models [17][18][19][20][21][22][23][24][25]. Addition of exogenous VEGF-D or VEGF-C also induces the formation of functional, mature collecting lymphatic collecting lymphatic vessels in mice [6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, adenoviral or transgenic overexpression of VEGF-D corrects defective lymphangiogenesis in airway inflammation in wild type mice [26] or in the skin of VEGF-C +/-lymphedema mice [14]. Vice versa, strategies to prevent VEGF-C/D mediated signaling block tumor (lymph)angiogenesis and metastasis in cancer, or lymphangiogenesis in corneal inflammation [5,21,23,27,28]. …”
Section: Introductionmentioning
confidence: 99%